THE HADITH OF ABU BAKRAH AND THE FUTURE OF WOMEN’S LEADERSHIP IN ISLAM - Ahmad Ainul Yaqin; Ahmad Musyafiq; Saichul Anam (Universitas Islam Negeri Imam Bonjol Padang, 2026)
The hadith narrated by Abu Bakrah, which states that “a nation that entrusts its affairs to a woman will never prosper,” has long been interpreted as a theological prohibition against women’s leadership in Islam. This interpretation persists despite significant changes in social structures and the increasing visibility of women in strategic leadership positions. This study seeks to reassess the normative status of this hadith by examining whether it represents a timeless religious injunction or a context-specific statement. Drawing on Fazlur Rahman’s double movement hermeneutics, the research employs a two-tiered analytical approach. The first movement situates the hadith within its socio-political context, particularly in relation to the aftermath of the Battle of the Camel and the decline of the Persian Empire. The second movement extracts the ethical values embedded in the hadith and reinterprets them in light of contemporary realities, emphasizing the principles of justice, merit, and public accountability. The findings indicate that the hadith was primarily a situational response to political instability rather than a categorical rejection of female leadership. Literalist interpretations tend to obscure the ethical intent of prophetic traditions and reinforce patriarchal biases that are inconsistent with the Qur’anic vision of justice and equality. This study concludes that a contextual and ethical reinterpretation of the hadith aligns more closely with Islamic moral philosophy and fosters a more inclusive theological discourse that recognizes and affirms the leadership potential of women in modern Muslim societies.